INDIKATOR MUTU PROGRAM PENDIDIKAN SEPANJANG HAYAT - Harina Yuhety; Yusufhadi Miarso; Anisah Baslemah (Jurnal Ilmiah Visi, 2008)
Considering the importance of lifelong education, this study aimed at obtaining the quality of lifelong education program in Indonesia. The study employed policy research method exploring the information from various sources. The findings of the study concluded that although the lifelong education program is not explicity stated in the education acts, its existance is undeniable conceptually and empirically.